(untitled) (Confluenţe Bibliologice, 2025)
University librarians gathered at Colloquia Bibliothecariorum Faina Tle-huci in Bălţi on February 23 for the fourth edition. Librarians Colloquium was inaugurated in 2013 in ex-director’s memory 40 years of Scientiﬁc Library USARB. At this event are invited outstanding academic and professional members of community from the country and abroad, all who knew or worked with Faina Tlehuci ,the distinguished librarian